PREDICTIVE FACTORS FOR RECURRENT GRAVES’ DISEASE AFTER TREATMENT WITH HIGH FIXED-DOSE RADIOACTIVE IODINE THERAPY - Huang , Shih Ming; Hung, Guang-Uei (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Failure rates of radioactive iodine (RAI) for treatment of Graves’ disease range from 10% to 40% depending on the region, patient characteristics and other factors. The purpose of this study was to investigate the predictive factors for RAI failure after treatment of Graves’ hyperthyroidism with fixed-dose RAI. METHODOLOGY Ninety-six patients with Graves’ disease who received 10 mCi or higher doses of RAI after failure of initial anti- thyroid drug (ATD) treatment with either propylthiouracil (PTU) or methimazole (Tapazole), were enrolled in this study. All patients had typical clinical presentation. RAI treatment was considered successful which euthyroidism or hypothyroidism was found after 1-year follow-up, without anti-thyroid drug usage. RESULTS The success rate of RAI therapy was 68% (65 out of 96 patients), while the failure rate was 32% (32 of total 96 patients). There was no significant difference between the success and failure groups regarding age, gender, thyroid functional status, and TSH receptor antibody. On the other hand, the failure group had a younger age at initial diagnosis, longer disease duration, and larger thyroid volume (all p < 0.05). In addition, we noticed that patients on PTU before RAI had a significantly higher failure rate (9 out of 15, 60%) than those on methimazole (22 out of 80, 28%). CONCLUSIONS We found age at diagnosis, duration of Graves’ disease, and thyroid volume as significant factors affecting the outcome of RAI treatment, which were consistent with observations of previous studies. Our study showed that treatment with PTU prior to RAI led to a significantly higher failure rate than treatment with methimazole.